Work Characteristics and Needlestick-Injury Status of Dental Hygienists - Yeon-Soon Park; Jeong-Hyun Lee; Jin-Soo Kim; Kyoung-Ok Yun; Sung-Suk Bae (치위생과학회지, 2024)
Background: Dental hygienists have a significant risk of infection due to occupational injuries caused by needles and sharp instruments. This study aimed to evaluate the current status of needle and “sharp-instrument injuries” among dental hygienists and to propose improved preventive guidelines. Methods: A total of 251 dental hygienists completed an online survey between August 1, 2023 and September 2, 2023. Data from 245 respondents were analyzed using IBM SPSS version 20, using independent t-tests and one-way analysis of variance to assess the frequency of injuries and their correlation with job characteristics. Results: Among the 251 dental hygienists, 77.6% had experienced needle or sharp-instrument injuries, with an average of 4.97 incidents per person. Infection prevention education significantly reduced the number of injuries, and participants with education exhibited better infection control practices than those without. Most injuries occurred during “instrument cleaning or maintenance” and “anesthesia preparation or disposal,” with “scalers, probes, and curettes” being the main culprits. Hands were the most frequently injured body parts. Conclusion: Preventive measures, continuous education, and improved guidelines are required to create a safer dental working environment.